Compensatory Hippocampal Neurogenesis in the Absence of Cognitive Impairment Following Experimental Hippocampectomy in Adult Rats - Cardoso, Giuliana T. M.; Gomes-Leal, Walace; Franco, Edna C. S.; Pereira, Antonio; Gomes, Francinaldo L.; Brino, Ana Leda F.; Lima, Silene M. A. (Frontiers in Cellular Neuroscience, 2021)
Temporal lobe epilepsy (TLE) is the commonest type of focal epilepsy in adult humans, and hippocampal sclerosis (HS) is the main pathological finding in this type of epilepsy. In refractory TLE, patients are indicated for unilateral resection of the affected hippocampus by a surgical procedure called hippocampectomy which generally does not cause any cognitive impairment. Once adult hippocampus is a region of endogenous neurogenesis, even in elderly people, we have hypothesized that a compensatory increase in hippocampal neurogenesis might occur in the remaining hippocampus after unilateral hippocampectomy. To test this hypothesis, we performed unilateral hippocampectomy in adult Wistar rats, which were perfused at 15 (G15) and 30 (G30) days post-surgery. Eighteen Wistar rats were randomly distributed in the following experimental groups: control (no surgery, N = 6), G15 (N = 6), and G30 (N = 6). Adjacent cortex and hippocampus of the left hemisphere were completely removed. Behavioral procedures were performed to address possible cognitive impairments. Brains were collected and fixed from animals belonging to all experimental groups. Gross histopathology was performed using thionine staining. Neuroblasts and mature neurons were immunolabeled using anti-doublecortin (DCX) and anti-NeuN antibodies, respectively. Numbers of DCX and NeuN positive cells were quantified for all experimental groups. Animals submitted to hippocampectomy did not present any cognitive impairment as evaluated by eight-arm radial maze behavioral test. The remaining hippocampus presented a higher number of DCX positive cells compared to control (p < 0.001, ANOVA-Tukey) at both G15 and G30. A higher number of NeuN positive cells were present in the granular layer of dentate gyrus at G30 compared to control and G15 (p < 0.001, ANOVA-Tukey). The data suggest that unilateral hippocampectomy induces compensatory neurogenic effect in the contralateral hippocampus. This may underlie the reported absence of significant cognitive impairment and parallels the findings in human patients submitted to unilateral hippocampectomy to treat refractory TLE.